Parents’ knowledge, attitude and practice in care of their asthmatic children at Hospital Universiti Sains Malaysia (Hospital USM) - Hamzah, Siti Noramarlinah (Universiti Sains Malaysia, 2014)
Asthma is a common chronic disease among children due to the immaturity of respiratory organs system. The management of asthmatic children must be taken seriously because asthma can cause morbidity and mortality among them. The objective of this study was to determine the level of parents' knowledge, attitude and practice in care of their asthmatic children. This study was conducted by using quantitative, descriptive and cross-sectional design. Respondents were recruited by purposive sampling among parents who have asthmatic children aged 6 until 12 years old at pediatric clinic Hospital USM (n=57). The self administered questionnaire was used to collect the data. The questionnaires consists 6 parts, part A and part F was with (yes/no) answer. Another part B. part C. Part D and part E was 3 choices (correct/incorrect/not sure) answer. For demographic data, descriptive statistics were used which comprises frequency and percentage. The mean age of respondents was 36.81 years. The majority of respondents (54.4%) score at moderate level of knowledge, had positive attitude (59.6%) and good level of practice (57.9%) in care of their asthmatic children. Fisher's Exact Test revealed significant association between knowledge and attitude (p< 0.01). knowledge with practice (p=0.01), previous exposure and level of knowledge (p=0.0l) and educational level with level of knowledge (p=0.043). However, there was no significant association between age and level of knowledge (p=0.696). In conclusion, there was a significant association between knowledge with both attitude and practice. Therefore, education regarding asthma must be enhanced to encourage successful practice in care of asthmatic children.